2018
DOI: 10.1177/1474904118790854
|View full text |Cite
|
Sign up to set email alerts
|

Relations between socio-economic risk factors, home learning environment and children’s language competencies: Findings from a German study

Abstract: This paper focuses on the influence of socio-economic risk factors and different aspects of the home learning environment in early childhood on children’s language competencies (vocabulary and grammar skills). The assumption is that children with more risk factors have lower competencies, but the home learning environment (measured by everyday activities at home and cultural activities) acts as a protective factor against risk. The data ( n = 2406 children) are a sample of the German National Educational Panel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 66 publications
0
12
1
Order By: Relevance
“…In contrast to previous studies (e.g., Melhuish et al, 2008;Kluczniok, & Mudiappa, 2018), the home learning environment was not related to vocabulary competence among children enrolled in this study. One reason might be that the composite measure of the learning environment was heterogeneous, including several different aspects (e.g., doing crafts, singing songs, activities with letters, visiting the library).…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…In contrast to previous studies (e.g., Melhuish et al, 2008;Kluczniok, & Mudiappa, 2018), the home learning environment was not related to vocabulary competence among children enrolled in this study. One reason might be that the composite measure of the learning environment was heterogeneous, including several different aspects (e.g., doing crafts, singing songs, activities with letters, visiting the library).…”
Section: Discussioncontrasting
confidence: 99%
“…Parental involvement is thus often seen as one way socio-economic status affects children's cognitive development. It has been demonstrated that parent-child learning activities positively affect children's language competence and vocabulary knowledge in the first years of primary education (Burchinal et al, 2002;Kluczniok & Mudiappa, 2018;van Steensel, 2006), pre-school literacy skills (Froiland et al, 2013), and general educational achievement (Castro et al, 2015). Specifically, reading books together seems to particularly facilitate vocabulary acquisition and early literacy skills (Scarborough & Dobrich 1994;Ewers & Brownson 1999;Sénéchal, 2006).…”
Section: Socio-economic Status Parental Education and Home Learning Environmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Historically, theorists looked to the family and eventually the overall home learning environment (HLE) as the factors that influence children the most (Bornstein, 2015). Many studies that used the HLE as a construct for predicting children’s development have shown that its quality influences children’s cognitive and socioemotional development (Kluczniok & Mudiappa, 2019) by examining the relationship between the HLE and children’s educational outcomes, especially for literacy and numeracy (Kluczniok et al, 2013). Research has shown the potential effect of the HLE on language (Boyce et al, 2013) and reading skills (Foster et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…In the life of the young child, the home environment is the most critical social setting in which such interactions take place. Studies have found, for example, that children acquire knowledge of language(s) through interactions with their parents, at home (Bornstein et al, 2020; DeLoache & DeMendoza, 1987; Kan et al, 2020; Kluczniok & Mudiappa, 2019; Moerk, 1985; Moerk & Moerk, 1979; Ninio & Bruner, 1978). According to Vygotsky’s (1978) theory of the zone of proximal development, parents’ fine-tuning of the level of language complexity and cognitive strategies parents use in speaking with their children can promote children’s internalization of these skills and strategies.…”
Section: Introduction and Purpose Of The Studymentioning
confidence: 99%